Leber's hereditary optic neuropathy clinical features in patients with mitochondrial DNA m.13513G>A candidate mutation - Andreeva, N A; Murakhovskaya, Yu K; Tsygankova, P G; Krilova, T D; Sheremet, N L (Vestnik oftal'mologii, 2022)
Leber's hereditary optic neuropathy (LHON) is caused by primary mtDNA by both primary mtDNA mutations and new mtDNA mutations. The last ones, when detected in several independent LHON families, receive candidate status. The description of new LHON-associated mtDNA mutation is relevant.Leber's hereditary optic neuropathy (LHON) is caused by primary mtDNA by both primary mtDNA mutations and new mtDNA mutations. The last ones, when detected in several independent LHON families, receive candidate status. The description of new LHON-associated mtDNA mutation is relevant.To determine the LHON clinical features in patients with the m.13513G>A mutation and to estimate the patients' proportion with this pathogenic variant in the LHON patients' sample.PURPOSETo determine the LHON clinical features in patients with the m.13513G>A mutation and to estimate the patients' proportion with this pathogenic variant in the LHON patients' sample.The study included 5 LHON patients, associated with m.13513G>A mutation in the ND5 gene in the heteroplasmic state. A standard examination was performed, including color blindness test, visual fields test, spectral optical coherence tomography.MATERIAL AND METHODSThe study included 5 LHON patients, associated with m.13513G>A mutation in the ND5 gene in the heteroplasmic state. A standard examination was performed, including color blindness test, visual fields test, spectral optical coherence tomography.LHON, associated with m.13513G>A in the heteroplasmic state in the range of 25-60%, is characterized by visual impairment without additional neurological or other extraocular symptoms. Visual recovery to 0.3-1.0 presents in all patients; the visual recovery onset occurs between 12 and 20 months from the disease manifestation. The decrease of the central scotoma size and its density and the color vision improvement are also observed as well as the average retinal nerve fibers layer and ganglion cell complex thickness decrease. The m.13513G>A mutation frequency is 5% in 100 LHON patients' sample and 22.5% in 22 LHON patients with rare and candidate mtDNA mutations.RESULTSLHON, associated with m.13513G>A in the heteroplasmic state in the range of 25-60%, is characterized by visual impairment without additional neurological or other extraocular symptoms. Visual recovery to 0.3-1.0 presents in all patients; the visual recovery onset occurs between 12 and 20 months from the disease manifestation. The decrease of the central scotoma size and its density and the color vision improvement are also observed as well as the average retinal nerve fibers layer and ganglion cell complex thickness decrease. The m.13513G>A mutation frequency is 5% in 100 LHON patients' sample and 22.5% in 22 LHON patients with rare and candidate mtDNA mutations.The m.13513G>A mutation can be considered as primary LHON mutation. The list of pathogenic variants recommended for testing LHON can include this mutation. The m.13513 G>A mutation determines the mild LHON course and good visual functions prognosis in these patients.CONCLUSIONThe m.13513G>A mutation can be considered as primary LHON mutation. The list of pathogenic variants recommended for testing LHON can include this mutation. The m.13513 G>A mutation determines the mild LHON course and good visual functions prognosis in these patients.